Влияние территориального фактора на стратегию обращения с ТБО - Сиволап, А.В. (Культура народов Причерноморья, 2014)
Всевозрастающий рост объемов твердых бытовых отходов (ТБО) оказывает негативного
воздействия на качество окружающей среды и, как следствие, требует разработки обоснованной
стратегии обращения с отходами. Но вопросам разработки региональной системы управления ТБО
уделяется еще недостаточно внимания.
Предлагается для разработки обоснованной стратегии обращения и разработки норм накопления ТБО
учитывать территориальный фактор, который определяется конкретными условиями: природные
условия (климатические, геологические); численность и соотношение городского и сельского населения;
уровень благоустройства жилого фонда и архитектурно-планировочные решения городов;
социокультурная характеристика населения (национальные традиции, уровень культуры,
благосостояние населения, состав семьи); наличие развитой инфраструктуры (конфигурация и
развитие дорожной сети, предприятия сферы обслуживания); специализация развития хозяйственного
комплекса.
Учет территориального фактора позволит повысить обоснованность разработки стратегии
обращения с ТБО. Всезростаючий зростання обсягів твердих побутових відходів (ТПВ) робить негативного
впливу на якість навколишнього середовища і, як наслідок, вимагає розробки обґрунтованої стратегії
поводження з відходами. Але питань розробки регіональної системи управління ТПВ приділяється ще
недостатньо уваги.
Пропонується для розробки обгрунтованої стратегії поводження і розробки норм накопичення ТПВ
враховувати територіальний чинник, який визначається конкретними умовами: природні умови
(кліматичні, геологічні); чисельність і співвідношення міського і сільського населення; рівень
благоустрою житлового фонду і архітектурно-планувальні рішення міст; соціокультурна
характеристика населення (національні традиції, рівень культури, добробут населення, склад сім'ї);
наявність розвинутої інфраструкту-тури (конфігурація і розвиток дорожньої мережі, підприємства
сфери обслу-говування); спеціалізація розвитку господарського комплексу.
Облік територіального фактора дозволить підвищити обґрунтованість розробки стратегії
поводження з ТПВ. The increasing growth of municipal solid waste (MSW) has a negative impact on environmental
quality and, consequently, requires the development of a sound waste management strategy. But the development
of a regional system of management of solid waste is given even less attention.
Are encouraged to develop sound management strategies and the development of standards for the accumulation
of solid waste to take into account the territorial factor.
Under territorial (associated with a particular territory) factor in the further refers to the level of its impact on
the treatment of MSW specific conditions that can be identified by the following features: environmental
conditions (climatic, geological); the number and proportion of urban and rural the population; the provision of
housing and architectural design of cities; social and cultural characteristics of the population (national
traditions, culture, welfare, family composition); the availability of infrastructure (configuration and
development of the road network, enterprises maintenance of residence); specialization development of the
economic complex. Of particular importance for the Crimea has the priority of economic development-government complex. The
increasing influx of tourists, tourists, tourists and visitors during the summer holiday season leads to a
significant increase in the volume of solid waste.
Accounting territorial factor will increase the validity of the planning at all stages - collection, use,
decontamination, transportation, placement of solid waste.